Coordination of Rheb lysosomal membrane interactions with mTORC1 activation - Angarola, Brittany (F1000Res, 2020)
A complex molecular machinery converges on the surface of lysosomes to ensure that the growth-promoting signaling mediated by mechanistic target of rapamycin complex 1 (mTORC1) is tightly controlled by the availability of nutrients and growth factors. The final step in this activation process is dependent on Rheb, a small GTPase that binds to mTOR and allosterically activates its kinase activity. Here we review the mechanisms that determine the subcellular localization of Rheb (and the closely related RhebL1 protein) as well as the significance of these mechanisms for controlling mTORC1 activation. In particular, we explore how the relatively weak membrane interactions conferred by C-terminal farnesylation are critical for the ability of Rheb to activate mTORC1. In addition to supporting transient membrane interactions, Rheb C-terminal farnesylation also supports an interaction between Rheb and the δ subunit of phosphodiesterase 6 (PDEδ). This interaction provides a potential mechanism for targeting Rheb to membranes that contain Arl2, a small GTPase that triggers the release of prenylated proteins from PDEδ. The minimal membrane targeting conferred by C-terminal farnesylation of Rheb and RhebL1 distinguishes them from other members of the Ras superfamily that possess additional membrane interaction motifs that work with farnesylation for enrichment on the specific subcellular membranes where they engage key effectors. Finally, we highlight diversity in Rheb membrane targeting mechanisms as well as the potential for alternative mTORC1 activation mechanisms across species.